E essa fila, será que anda? Acesso à educação infantil no município de Cascavel (PR) - Neves, Antonella Marques (2019)
This research has as its theme the access to Early Childhood Education in the city of Cascavel - PR. The objective was to understand the applicability of constitutional norms regarding the rights to early childhood education. The research was carried out in three moments: bibliographic research, documentary research and field research. In the bibliographic research the historical and political aspects of the legislative changes regarding the kindergarten were approached. In the documentary research, a data analysis was carried out at the Municipal Secretariat of Education of Cascavel, State of Paraná on the records of waiting for vacancies in CMEIS (queue) with a view to presenting a diagnosis of the problem. The field research was carried out by analyzing the numbers of parents of children who are waiting in line for vacancies and also those who recently got a place at CMEIS in the city of Cascavel through the court. Questions will be raised regarding the effectiveness of laws in the area of early childhood education in the municipality, as well as expectations regarding early childhood education, analyzing both the inclusion of children in the CMEIS and the conditions of infrastructure. Data analysis was performed based on the phenomenological principles of data description and analysis related to access to early childhood education. Among the results found, we highlight that the problem covers the national scope with differentiated alternatives for solving problems that are far from meeting the real demand. In Cascavel the alternatives to meet the demands are partnerships with NGOs, transparency in queues and the creation of new vacancies.